Other people's rules. (Economist, 2015)
The article focuses on the political impact that former U.S. Secretary of State Hillary Clinton's use of a personal email account during her tenure as Secretary of State, and her later deletion of emails on the server, have had on attitudes of American voters on how trustworthy she is and their lack of enthusiasm on her campaign.